Treatment of Class Ii Malocclusion with Klammt Appliance: Clinical Case Report - Borja de Melo, Téssia Richelly Nóbrega; Souza Filho, João Paz De; Guimarães, Raquel da Silva (The Journal of Dentists, 2023)
Objective: to report a clinical case of a young patient with Class II malocclusion, treated with the Klammt II Elastic Activator device, emphasizing the benefits of early treatment through Facial Jaw Orthopedics. Case Report: patient G.N.S., Class II division 1, female, caucasian, Brazilian, 10 years and 10 months old, with good oral health, mixed breathing and onychophagia, attended the teaching clinic of UNIFIP/ Brazil, for orthodontic treatment due to aesthetic dissatisfaction. After clinical evaluation and radiographic and cephalometric examinations, a Class II, division 1 malocclusion with retruded mandible was diagnosed. The Klammt II functional orthopedic appliance was prescribed, with full use, for a period of 12 months and bimonthly appointments. The evolution of the case was satisfactory, with mandibular advancement and satisfactory change in the patient's facial profile. Conclusion: it is concluded that the Klammt II open elastic activator minimized the damage caused by class II division 1 with mandibular retrognathism, redirecting the growth of the mandible in a functional way, thus generating psychological benefits and favorable aesthetics for the profile and facial proportionality.